Students’ Perspective on Teaching Materials of English for Management Business II In Management Department, Universitas Muria Kudus - Nuraeningsih, Nuraeningsih (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2019)
In the era of globalization, people around the world can have interaction for satisfying their goal in any aspect of life, such as business, politics, social and culture, education, etc. for that reason, the need of English proficiency as a global language becomes a priority. Therefore, it is compulsory for all students in formal education to learn it. In university level, students of the non-English department must study English with varied purposes, depending on their major, at least for two credits. Generally, it is taught to support the basic major or discipline. Consequently, the materials are designed based on their needs, especially later when they get jobs. For this reason, the material adapted is called ESP (English for Specific Purposes) which aims at preparing students to meet the demands of the workplace, i.e. the English skills. It should be more contextual, real life for now and the future. If the material is authentic and in accordance with the needs of learners, they will likely be ready to work as the demands of the employer. With these objectives, the English materials need to be adjusted to the needs of users (stakeholders) so that after graduating from universities, freshmen can directly work or create jobs according to their expertise. This research aims to describe students’ perception of English teaching materials for Management department. A survey was conducted to second-semester students of Management department of Universitas Muria Kudus. The result of the study reveals that the students have a positive perspective on the teaching materials of English for Management Business II. They think affirmatively that the materials have been selected properly in terms of material attraction, usefulness, authenticity, variety, level of difficulty, language skill proportion and the discussed topics. In other words, the materials are appropriate for satisfying Management department students’ need to prepare their future. The implication is the materials should be revised by adding more reading texts of Business English and providing more vocabulary tasks in the real context.